2019
DOI: 10.29309/tpmj/2019.26.11.3224
|View full text |Cite
|
Sign up to set email alerts
|

Upper GI bleeding: Causes, morbidity and mortality in admitted patients at Tertiary Care Hospital of Karachi.

Abstract: Objectives: Acute upper gastrointestinal bleed is one of the most common emergencies. Despite advancement in the medical field, gastrointestinal bleeding still carries significant mortality and fiscal burden on healthcare system. At present, limited data is available on the predictors of morbidity and mortality associated with acute upper gastrointestinal bleeding in our part of the country. Study Design: Descriptive analytical study. Setting: Medical wards of Civil Hospital Karachi. Period: From January 2018 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Most of the local studies elaborating on mortality have reported combined mortality of PUB along with oesophagal variceal bleeding. However, one such study reported an even higher mortality (26.7% for non-variceal bleeding)[ 22 ]. In the current study, one-week and one-month mortality stood at approximately 11% and 15%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the local studies elaborating on mortality have reported combined mortality of PUB along with oesophagal variceal bleeding. However, one such study reported an even higher mortality (26.7% for non-variceal bleeding)[ 22 ]. In the current study, one-week and one-month mortality stood at approximately 11% and 15%, respectively.…”
Section: Discussionmentioning
confidence: 99%